Superman and the quest of the Aristotelian way - Gelson Vanderlei Weschenfelder
One of the most remarkable phenomena of popular culture today is the strong resurgence of powerful superhero comics, which however are not as innocent as they seem. Not only do they bring fun for the reader, they introduce and vividly discuss the very important issues faced by humans, relating to ethics, personal and social responsibility, and citizenship rights. Superman one of the most popular superheroes in the world comics, and one of the first to appear, brings these issues in the stories. The attitude of this superhero addresses so experienced, ethical issues countersigned the Greek philosopher Aristotle.